Letters as ‘Documents of Life’ ‒ the Author’s Proposal of a Method for Analysing Epistolary Narrative (MANE) in Andragogical Research (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
Letters as a source of data for qualitative research are not a commonly used research material, although written statements in the form of diaries, journals or just correspondence have been present in research practice in the field of many social science and humanities disciplines for years. Letters, however, represent a large and underused research potential especially for qualitative analyses. The author’s method of analysing documents produced in the form of letters presented here provides a universal framework and inspiration, as well as a description with justification of the implementation of the subsequent stages of the research procedure. The person using the MANE method is at thesame time the creator of his/her own research project, adapting it to his/her own goals. Atthe same time, the methodology of the research procedure and analysis is accompanied bymany examples from completed research projects - mainly in the field of adult education.It provides a basis for action for researchers wishing to broaden their skills as qualitativeresearchers.